The Balance and unbalance in alliance relations The Saudi Arabia and United State Relation as model: The Balance and unbalance in alliance relations The Saudi Arabia and United State Relation as model (Journal of the College of Education for Women, 2019)
Abstract:Saudi Arabia and United States long relation could present an importantsubject to understand alliance kind in international relations types. We tryingin this study to diagnose and analyze the Saudi Arabia and United Statesmodel to find balance and unbalance statues and its influence on thedirections of Saudi Arabia foreign policy positions.We divided the study in two parts, each part have many sections. Thefirst part deal with the historian emergence of Saudi Arabia state and itsdevelopment in three stages including its foreign relations with regions andinternational powers. While the second part was dedicated in analyzing andunderstanding the mechanism and active facts that drawing the Saudi Arabiaforeign policy toward American United State.We find that the relation have unbalance attribute relate in structuremethod of the third Saudi Arabia state that different of the first one whichestablished according to a local deal between a cleric man and a tribe sheikwhile the third state building according a mix of local , region and internationalfacts. The fails of the foreign policy of first state reflects negatively on the mindof third state decision maker. This fear pushes him to try to protect his state byenforce its relation with international powers neglecting its sovereignty whichmake him weak in many fields.Saudi Arabia foreign policy will be always an important subject need tounderstand from us because it's an important state in the region.